The Effect of Breastfeeding and an Intensive Breast Milk Nutritional Support Program on Hospitalization Rates for Hyperbilirubinemia in Term Newborns: An Open Randomized Controlled Trial. (25th March 2022) - Cinar, Nursan; Karakaya Suzan, Özge; Caner, Ibrahim; Peksen, Sultan; Tabakoglu, Pinar; Cinar, Vedat
ABSTRACT: Objective: The aim of this study was to determine the effect of breastfeeding and intensive breast milk nutritional support program (IBNSP) on hospitalization rates for hyperbilirubinemia in normal term newborns. Methods: This study's sample consisted of 68 newborn infants (experimental group: 34; control group: 34) born at a university hospital from October 2020 to April 2021. Five steps of breastfeeding and IBNSP were administered to the experimental group for the first 48 h after birth. This program starts at the postpartum first hour and continues until the 48th hour. It includes face-to-face training, practical support on breastfeeding, and one-to-one demonstration and practice methods. The control group received the standard care recommended by the World Health Organization. Both groups' bilirubin levels were measured 24 and 72 h after birth. Participants in both groups were hospitalized for risky (according to bilirubin values) situations. The groups' bilirubin levels and hospitalization rates for hyperbilirubinemia were compared. Results: There was no statistically significant difference between the experimental (5.19 ± 1.27) and the control (5.83 ± 1.52) groups' bilirubin levels at 24 h after birth, ( t = −1.881, p = 0.064); however, the control group infants (12.03 ± 3.67 mg/dl) had higher bilirubin levels than the infants in the experimental group 72 h after birth (9.55 ± 2.82 mg/dl) ( t = −3.122, p = 0.003). The experimental group's hospitalization rate for hyperbilirubinemia ( n : 1, 2.9%) was lower than the control group's rate ( n : 8, 23.5%), and this difference was statistically significant ( X 2 = 6.275, p = 0.014). Conclusions: Breastfeeding and IBNSP effectively prevent hospitalization for hyperbilirubinemia and reduce newborns' bilirubin levels.